Kingdom of Bhutan: sovereignty against backdrop of «ethnic conflicts» in Tibetan border of India and China. 1947–2004 - M. S. Novikov; S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
For tourists the region is associated with Buddhist and Hindu shrines. Therefore, the Indian states located in the Himalayas, as well as the states of Nepal and Bhutan, attract a large number of travelers. This is a region with a difficult military-political situation. The Himalayas — this is the border between the People’s Republic of China and the Republic of India, the influence of Pakistan and Bangladesh also affects. The region is not politically stable, there is a sluggish war of numerous and ideologically very different military-political organizations against the government forces of India